Avaliação da utilização de polímeros superabsorventes residuais com fibra ceulósica como agente de cura interna em concretos: ensaios laboratoriais e aplicação em escala real - Cardoso, Bruno Henrique (Universidade do Vale do Rio dos Sinos, 2023)
Reinforced concrete can suffer different types of pathological manifestations, including different types of cracks. This type of manifestation is as harmful as the others, and may be the one that most needs observation, because the moment a fissure occurs, a door opens for the appearance of other forms of pathological manifestations. In the fresh state, in order to minimize the occurrence of surface desiccation cracks and drying shrinkage, curing of the concrete must be started immediately after concreting, normally spraying water in order to keep the concrete moist and prevent water from entering the interior. of the same evaporate. . In this work, a residual superabsorbent polymer (PSAR) was used, having its origin in the production of hygiene products. Along with this material there is also the presence of cellulosic fibers, which are part of the original product, and which can help to reduce shrinkage. PSAR has great potential for use as an internal curing agent, as seen in previous studies, where it was applied in pastes and mortars. Having as objective the practical use of the material, this work evaluates its behavior in concrete, evaluating the effects of internal curing both in the fresh state (superficial desiccation), using tests by Girotto, Barbosa and Maciel (2014), where they performed an adaptation of Turcry ( 2004) and by Saliba et al. (2011), as for the hardened (mechanical strength and free retraction), through the NBR 5739:2007 and the American standard the ASTM C157 standard, and finally its porosity verifies through the RILEM TC 116 PCD standard (1999). This research also presents the first real-scale field study carried out, where the behavior of the material on a concrete floor on the outside of a concrete mixer is verified. The results show that the material contributes positively, reaching a reduction of approximately 2.7 times in plastic shrinkage tests. The mechanical strengths, on the other hand, obtained lower values compared to the reference mix for poor mixes, however, in rich mixes. In the porosity tests it is seen that in curing conditions with low humidity the internal curing agent demonstrates a better efficiency. In field tests, this difference in values is also very noticeable, where the trace with the addition of polymeric material almost does not show cracks, however, in the reference trace, it has an average of 9 cm in length spread throughout its area.
Keywords: Concreto; Polímero superabsorvente; Retração; Cura interna; Concrete; Superabsorvent polymer; Retraction; Internal curing; ACCNPQ::Engenharias::Engenharia Civil